A high effective CuInS2 photocatalyst for oxidative desulfurization of dibenzothiophene in fuel oil - Pham, Nui Xuan; Pham, Thi Thanh; Vo Hoang, Thuy Vy; Nguyen, Thi Duyen; Thanh Lam, (Vietnam Journal of Science and Technology, 2025)
In this study, CuInS2 materials were synthesized by hydrothermal method. The effect of the different reaction times have been investigated. The structure and morphology of the materials were characterized by XRD, SEM, TEM, UV-Vis and EDX measurement methods. The obtained results showed with reation time at 24 h, the CuInS2 sample (CIS-24) has an average particle size of about 50 nm and a band gap energy value of Eg=1.48 eV, which has the ability to strongly absorb visible light. The photocatalytic activity of the CIS-24 was investigated by degradation of dibenzothiophene under visible light irradiation. The photocatalytic efficiency reached a maximum of 97.9% after 5 h of reaction temperature at 70 oC with 50 mg of the catalyst dosage and 1,0 mL of H2O2 as oxidant.